Trouble at the bar : an economics perspective on the legal profession and the case for fundamental reform /: an economics perspective on the legal profession and the case for fundamental reform. ([2021]) - Winston, Clifford, 1952-; Burk, David; (Economist), Yan, Jia
No abstract available